Corporate Governance Quality and Earnings Management in Nepalese Insurance Companies - Neupane, Samikshya; Giri, Shreya; Chhetri, Sumita; Shahi, Suraj; Dahal, Yasodha (Nepalese Journal of Management, 2025)
The study examines the effect of corporate governance quality on earnings management in Nepalese insurance companies. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are board size, independent director, women director, government ownership, foreign ownership and insurance size. The study is based on secondary data of 15 insurance companies with 105 observations for the period from 2015/16 to 2021/22. The data were collected from the annual reports of the selected insurance companies and annual report published by Rastriya Beema Authority. The regression models are estimated to test the significance and effect of corporate governance quality on the earnings management of Nepalese insurance companies. The study showed that independent director has a positive impact on return on assets and return on equity. It implies that increase in number of independent directors in board leads to increase in return on assets and return on equity. Similarly, women director has a negative impact on return on assets and return on equity. It implies that increase in number of women directors in board leads to decrease in return on assets and return on equity. However, board size has a negative impact on return on assets and return on equity. It means that increase in board size leads to decrease in return on assets and return on equity. Similarly, government ownership has a negative impact on return on assets and return on equity. It shows that increase in government ownership leads to decrease in return on assets and return on equity. Similarly, foreign ownership has a positive impact on return on assets and return on equity. It implies that increase in foreign ownership leads to increase in return on assets and return on equity.